(3QSGdI aj CbQGQ GdRhL HWdGb RhLJgs - (3GdbRhjfj GdMGFQj, eMeO MSjf Hf Ydj GdWGdbGfj GdbRhjfj GdMGFQj, J (B1281(3g` (B1864(3es ((3fhQhR GdWGQejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3eSFdI gd jbHd GdRhL HWdGb RhLJg HGdfSHI EdjgG hjfaP aj MbgG hMb HGbj GdCRhGLs
(3BNQgG (B:s
(3BNQgG(B: (3bGYOI chf GdbGOQ Ydi EfTGA eSei ebHhd Gdbhd ajg Ydi fMh GdcdjI eSdeJjf aj LejY GdehGQO NdGaG dUGMH ebGHS GdCfhGQ MjK LYdgG bGYOJjf eSdeJjf YfOge haQY YdjgG aQhkYG cKjQI hdcf GdMb eG GNJQfGg hPcQfGgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf L (B3: 255s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis